Recent advances in electrochemical recovery of rare earth elements from NdFeB magnets - Fu, Li; Karimi Maleh, Hassan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Recent advances in electrochemical methods show promise for more sustainable recycling of rare earth elements (REEs) from end-of-life NdFeB permanent magnets. Demand for NdFeB magnets is rapidly growing for clean energy applications, motivating recycling efforts to diversify REE supplies. Core electrochemical steps involve selective dissolution of REE-rich phases at the anode and reduction of REE ions at the cathode. Pretreatment including demagnetization, mechanical size reduction, and leaching help liberate and concentrate the REEs. Thermal demagnetization and mechanical crushing make the magnets brittle and improve leachant penetration. Acid leaching dissolves REEs but co-dissolves iron. Molten salt electrolytes such as chlorides enable high temperature REE recovery while ionic liquids allow milder conditions but can decompose. Aqueous solutions have been most thoroughly investigated for versatility and affordability. Cathode materials like titanium, molybdenum, and stainless steel facilitate REE deposition while avoiding co-reduction of iron and cobalt. Additional purification is needed to isolate high purity REE oxides and metals, using techniques like solvent extraction, selective precipitation, and electroseparation. Key factors for optimal electrochemical recycling are maximizing selectivity for REEs, minimizing energy use and waste generation, and simplifying integration. While technical challenges remain, recent advances demonstrate electrochemical technologies can improve the sustainability of recycling critical REEs from permanent magnets.